The thinking process of Football coaches: The training factors - Carvalho, G.; Rodrigues, J. F. (Journal of Human Sport & Exercise, 2019)
This research is a qualitative study with focus on the thinking process of the Football coaches, related to the training factors. We interviewed ten coaches, with recent experience in the First and Second Portuguese Professional Football Leagues. The data collected was treated using the MAXQDA 2018® software. The analysis performed highlights that all participants indicate work the training factors in an integrated manner. They assume the importance of psychological factors for a constant sport performance. We are led to conclude that the approach to the training factors is related to the thinking process of the coach, materialized through the planning set, in the thoughts and interactive decisions, as well as in their beliefs and reflexions.